2013
DOI: 10.1007/s13105-013-0260-9
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic differentiation of mouse iPS cells and analysis of liver engraftment potential of multistage iPS progeny

Abstract: Hepatocyte transplantation is considered a promising therapy for patients with liver diseases. Induced pluripotent stem cells (iPSCs) are an unlimited source for the generation of functional hepatocytes. While several protocols that direct the differentiation of iPSCs into hepatocyte-like cells have already been reported, the liver engraftment potential of iPSC progeny obtained at each step of hepatic differentiation has not yet been thoroughly investigated. In this study, we present an efficient strategy to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…The minimal ureagenesis observed in the Arg1 Δ hepatocytes is likely residual expression resulting from incomplete tamoxifen-mediated removal of exons 7 and 8. Nevertheless, our observations are in accordance with a previous report that showed consistent expression of Afp accompanied by low Arg1 expression and urea synthesis at the final stage of differentiation relative to primary hepatocytes 29 . To evaluate the expression of other urea cycle enzymes, we performed quantitative real-time PCR (qRT-PCR) and observed scarce expression of the five main ureagenic enzymes, providing further evidence of incomplete maturation (Fig.…”
Section: Resultssupporting
confidence: 94%
See 2 more Smart Citations
“…The minimal ureagenesis observed in the Arg1 Δ hepatocytes is likely residual expression resulting from incomplete tamoxifen-mediated removal of exons 7 and 8. Nevertheless, our observations are in accordance with a previous report that showed consistent expression of Afp accompanied by low Arg1 expression and urea synthesis at the final stage of differentiation relative to primary hepatocytes 29 . To evaluate the expression of other urea cycle enzymes, we performed quantitative real-time PCR (qRT-PCR) and observed scarce expression of the five main ureagenic enzymes, providing further evidence of incomplete maturation (Fig.…”
Section: Resultssupporting
confidence: 94%
“…4d). These data suggested that either the cells were not mature enough for high-level Arg1 expression by the chosen differentiation protocol 29 and/or that there were problems with maturation of the RFP fluorophore (see Discussion).
Figure 4Generation of hepatocyte-like cells from repaired mouse iPSCs. ( a ) Schematic diagram showing the stepwise hepatic differentiation protocol.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of them grew normally in THAG but not in ACG (Figure S7, Supporting Information). Remarkable epithelial morphogenesis was recapitulated in the neo‐tissues formed in the cell‐laden THAG, where Caco2 and Hep G2 cells developed into tubal organoids ( Figure 5 a,c, Figures S8 and S9, Supporting Information) 35, 36. IF co‐staining for human retinol‐binding protein II (RBP 2) or human hepatic nuclear factor 4 alpha (HNF 4α)—markers of Caco2 and Hep G2 cells,34, 37 respectively—and E‐cadherin further testified that the tubular structures were constituted by the formed epithelium organoids (Figure 5b and d).…”
Section: Resultsmentioning
confidence: 96%
“…Although a variety of hepatic differentiation methods have been established in mouse and human iPSCs [14], [15], [16], less attention has been paid to iPSC-derived from large animals such as pigs. The efficent production of hepacocytes from iPCSs is heavily reliant on the deep understanding of early stage hepatogenesis.…”
Section: Discussionmentioning
confidence: 99%